2022
DOI: 10.3389/fphys.2022.912797
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental tannic acid on growth performance, gut health, microbiota, and fat accumulation and optimal dosages of tannic acid in broilers

Abstract: This study was conducted to investigate the effects of different dosages of tannic acid (TA) on growth performance, nutrient digestibility, gut health, immune system, oxidative status, microbial composition, volatile fatty acids (VFA), bone mineral density, and fat digestion and accumulation in broilers and to find optimal dosages of TA for efficient growth and gut health in broilers. A total of 320 male Cobb500 broilers were randomly distributed to 4 treatments with 8 replicates including 1) tannic acid 0 (TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…The dosage effect of TA on the growth performance of broilers seems to be unclear. However, it is reported that high dose of TA has negative effects on the growth of broilers, and biological effects are strongly dose-dependent (37,38). Redondo et al (39) hypothesized that the addition of excessive TA to the diet may increase the astringency and bitterness of the feed, thereby reducing the feed intake.…”
Section: Discussionmentioning
confidence: 99%
“…The dosage effect of TA on the growth performance of broilers seems to be unclear. However, it is reported that high dose of TA has negative effects on the growth of broilers, and biological effects are strongly dose-dependent (37,38). Redondo et al (39) hypothesized that the addition of excessive TA to the diet may increase the astringency and bitterness of the feed, thereby reducing the feed intake.…”
Section: Discussionmentioning
confidence: 99%
“…The quantity and quality of extracted DNA were confirmed by using a NanoDrop 2000 spectrophotometer (Thermo Fisher Scientific, Waltham, MA). The 16s rRNA gene sequencing was assisted by LC sciences, LLC (Houston, TX) ( Choi et al, 2022b ). QIIME2 (version 2022.02) was used to analyze sequenced data ( Bolyen et al, 2019 ; Choi and Kim, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Reduced AA digestibility may lead to decreased meat yield because AAs are building blocks for proteins in meat [ 52 ]. Our previous study demonstrated that E. tenella infection reduced the production of cecal short-chain fatty acids (SCFA; an important energy source for the host), which can lead to energy imbalances and reduce fat accumulation, resulting in decreased meat yields among broiler chickens [ 53 , 54 ]. Induced inflammation and oxidative stress caused by Eimeria infection can negatively affect meat quality in broilers [ 55 , 56 ].…”
Section: Challenging Conditions In Broiler Production Are Associated ...mentioning
confidence: 99%
“…The microbiota of the gastrointestinal tract of broiler chickens plays an important role in producing SCFA, which is an important energy source for the host [ 53 ]. Increased SCFA production levels, due to beneficially modulated microbiota, can affect the fat accumulation and body composition of broiler chickens [ 54 ]. However, a previous study by Wang et al [ 163 ] showed that the supplementation of Lactobacillus johnsonii BS15 (1 × 10 6 CFU/kg feed) reduced fat accumulation by downregulating fat accumulation-related genes (e.g., lipoprotein lipase) in adipose tissue and by upregulating hepatic genes related to fatty acid β-oxidation in broiler chickens.…”
Section: Effects Of Nutritional Interventions On the Meat Quality Of ...mentioning
confidence: 99%
See 1 more Smart Citation